2015
DOI: 10.1016/j.marchem.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Delayed settling of marine snow: Effects of density gradient and particle properties and implications for carbon cycling

Abstract: Marine snow aggregates are often a dominant component of carbon flux and are sites of high bacterial activity; thus, small-scale changes in the settling behavior of marine snow can affect the vertical locations of carbon export and remineralization in the surface ocean. In this study, we experimentally investigated the sinking velocities of marine snow aggregates formed in roller tanks as they settled through sharp density gradients. We observed between 8 and 10 aggregates in 3 different experiments, each of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 38 publications
1
66
0
Order By: Relevance
“…This calculation in turn depends on the relative lability of the organic carbon in the sinking particles (Engel et al, 2009), the hydrolytic capacities of the microbial communities acting on them as they sink, the extent of water column stratification, and the residence time of the particle at different depths (Prairie et al, 2015). Holding all other factors constant, the biological pump would be more efficient at less stratified stations-such as stations 2, 4, and 7-where a larger proportion of the hydrolytic capacity occurs in the mesopelagic zone, below the permanent thermocline (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…This calculation in turn depends on the relative lability of the organic carbon in the sinking particles (Engel et al, 2009), the hydrolytic capacities of the microbial communities acting on them as they sink, the extent of water column stratification, and the residence time of the particle at different depths (Prairie et al, 2015). Holding all other factors constant, the biological pump would be more efficient at less stratified stations-such as stations 2, 4, and 7-where a larger proportion of the hydrolytic capacity occurs in the mesopelagic zone, below the permanent thermocline (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…An important consideration is that the density gradient used in delayed settling measurements for GP1-early exponential and GP2-late exponential was sharper than that used in delayed settling measurements for GP3-early stationary and GP4-late stationary, so the delayed settling time for aggregates between these pairs of growth phases may not be comparable. However, delayed settling time for aggregates is typically longer when passing through sharper density gradients [22], and so if the delayed settling measurements in GP3-early stationary and GP4-late stationary were conducted with an equally strong density gradient as the earlier growth phases, the delayed settling times would likely be even greater. The increased delayed settling time at later growth phases is expected given a previous experimental study that found longer periods of decreased velocities through sharp density gradients for aggregates of lower densities [22].…”
Section: Discussionmentioning
confidence: 99%
“…In all experiments, aggregate excess density was measured for aggregates in each growth phase by quantifying the size and settling velocity of individual aggregates following the method described in References [21,22]. In Experiments 3 and 4, the aggregates were very fragile for some of the growth phases resulting in lower sample sizes (Table 1); it is possible that in these experiments, aggregate density measurements may have been biased because aggregate density could not be quantified for the more fragile aggregates which may have been less dense on average.…”
Section: Measuring Aggregate Excess Densitymentioning
confidence: 99%
See 2 more Smart Citations